Pengaruh Penerapan Model Pembelajaran Kontekstual Berbantuan Media Flash Terhadap Pemahaman Konsep Fisika Siswa - Akbar Riyadi; Gunawan Gunawan; Jannatin Ardhuha (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2015)
This research is a quasy experiment which aimed to finding out the effect of contextual learning model implementation assisted by media flash on the understanding concept of physics in SMPN 1 Labuapi. The population is all class VIII which filled by 117 students, while the sample of this research is class VIII B with 23 students as experiment group and grade VIII C with 23 students as control group. The sampling technique used is purposive sampling. The research design used is nonequivalent control group design. The hypothesis is tested by t-test separated varians. Based on by calculation hypothesis testing obtained that there is a difference of understanding concept of physics between experiment group which is given treatment with contextual learning model assisted by media flash and control group which is given treatment as convensional learning. The mean of the posttest for experiment group is greater than control group, so it can be obtained that contextual learning model assisted by media flash given positive result for understanding concept of physics in grade VIII SMPN 1 Labuapi. N-gain test given that for all of sub materi of light showed that the increasing of understanding concept of physics of class experiment is higher than control class, so it can be obtained that the increasing of understanding concept of physics of experiment group is higher than control group.